Constructing Religious Organization Collective Identity through Online Media Coverage of Prevention and Handling of Sexual Violence Discourse - Irdiansyah, Achmad Ramdhany (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2023)
This research aims to examine how two religious organizations, Nahdlatul Ulama (NU) and Muhammadiyah, have constructed their collective identity through online media coverage about the discourse of preventing and addressing sexual violence (PPKS). In this regard, this research analyses news stories published by NU.or.id and Muhammadiyah.or.id regarding PPKS discourse. Using a qualitative textual analysis method with thematic analysis and rhetorical analysis approach, the findings have revealed that NU and Muhammadiyah construct their collective identities as da'wah movements, civil society organizations, and cultural groups. As da'wah movements, NU and Muhammadiyah have conveyed their ideas about sexual violence rooted from Islamic values. As a civil society organization, NU has shown symbolic actions that utilize social capital, while Muhammadiyah has expressed through organization programs. As a cultural group, NU has used cultural memory in the form of istigasah kubra, sowan tradition, and Islamic boarding school activities. Meanwhile, Muhammadiyah has used cultural memory in the form of symbols of da'wah works, schools, and campuses to represent itself as a community service and da’wah movement.